AB1017 Vertebral fractures are likely to occur in lumbar vertebra in patients with osteoporosis and even in osteopenia. (12th June 2018) - Jiang, Y.; Lin, D.; Guo, X.; Zhao, M.; Fang, L.; Chen, Z.; Li, X.; Zheng, X.; Liao, Z.; Gu, J.
Abstract : Background: Osteoporosis is a common disease, which can lead to fracture. New diagnosis includes fracture of the vertebral bodies and hips, T-scores of bone mineral density (BMD) less than 2.5 or osteopenia together with humeral, forearm or the pelvis facture. Vertebral assessment should be considered in some conditions. 1 Objectives: Our study was to investigate the condition of osteoporosis in patients who underwent bone mineral density in our hospital and fracture status according to lateral X-ray of cervical, thoracic and lumbar vertebra. Methods: Patients were enrolled from September to December in 2017 in the Third Affiliated Hospital of Sun Yat-sen University. Demographic information, past medical history, and clinical information were collected by two rheumatologists. Bone mineral density measured by Dual Energy X-ray Absorptiometry was performed based on clinical needs. Patients with osteoporosis or osteopenia were asked to have X-ray scan of cervical, thoracic and lumbar vertebra. The Statistical Package for Social Sciences (SPSS) software version 21 was used for all data management and analysis. Results: Of all the 210 patients, 60 (28.6%) were male patients. 59.5% of female patients were in post-menopause stage. Mean age was 57.60±13.17 years.124 patients were asked to perform BMD by the rheumatologists. 20 patients did the test after they saw an endocrinologist. 40 patients did the test after they saw an orthopedist. 102 patients had T-scores less than 2.5. 61 patients had osteopenia according to BMD. 22 patients had fracture according to past history or X-ray scans' findings. 10 patients had multiple fractures. The most frequent fractures were located in L1 (nine patients) and L2 (four patients). The other parts included L3, L5, C7, T12, T6, T8, and T9. Two patients had ankle or humeral fractures before because of injury. Vertebral fractures were founded in 5 (8.2%) of the patients with T-scores of −2.5 to −1 during this study. Conclusions: Lateral X-ray scans of the vertebra can detect vertebral fractures in patients with osteopenia according to BMD scores, even in patients less than 50-year-old. Osteoporosis could be underestimated without measurement of the vertebra. The most frequent vertebra fracture happens in L1. Reference: [1] Gallacher SJ, Gallagher AP, McQuillian C, Mitchell PJ, Dixon T (2007) The prevalence of vertebral fracture amongst patients presenting with non-vertebral fractures. Osteoporos Int18, 185–192. Disclosure of Interest: Y. Jiang: None declared, D. Lin: None declared, X. Guo: None declared, M. Zhao: None declared, L. Fang: None declared, Z. Chen: None declared, X. Li: None declared, X. Zheng: None declared, Z. Liao Grant/research support from: National Natural Sciences Foundation of China [grant number 81201372], J. Gu Grant/research support from: the 5010 Subject of Sun Yat-sen University (2007023)